Development of time controlled chronomodulated tablet with swelling and rupturable layers: Optimization of factors influencing lag‑time and drug release - Desai, Mayur; R Jivani, Rishad; D Patel, Laxman; P Jivani, Noordin; Sonagara, Bhavin (International Journal of Pharmaceutical Investigation)
Introduction: A tablet system consisting of cores coated with two layers of swelling and rupturable coatings was prepared and evaluated as time controlled chronomodulated tablet. Materials and Methods: Cores containing Montelukast sodium as model drug were prepared by direct compression and then coated sequentially with an inner swelling layer containing a HPMC E 5 and an outer rupturable layer of Eudragit RL/RS (1:1). A three‑factor, two‑level, full factorial design was used to investigate the influence of amount of HPMC E 5 and Eudragit RL/RS (1:1) on the responses, i.e., lag time to release and time required for 80% of drug to releases. The dissolution tests were studied using the USP paddle method at 50 rpm in 0.1 N HCL for 2 hr and than in phosphate buffer pH 6.8. Result: The lag time of the drug release decreased by increasing the inner swelling layer and increased by increasing the rupturing layer level. Conclusion: The results obtain from present study suggest that swelling come reputable coating approach gives desire drug release after lag time.
Keywords: Asthma; cronomodulated drug delivery; Montelukast sodium; swelling layer